Design, Synthesis and Biological Evaluation of 2‐(naphthoyl) iminothiazolidin‐4‐ones as Potential Anticancer Agents. Issue 13 (2nd April 2020) - Ashraf, Saba; Saeed, Aamer; Moon, Seong‐Hee; Flörke, Ulrich; Kim, Seong Hwan; Ashraf, Zaman; Yaseen, Muhammad; Latif, Muhammad
Abstract: A library of novel naphthyl bearing 2‐iminothiazolidin‐4‐ones (2‐ITZDs) (2  a –2  q ) was designed and synthesized through a facile route involving regioselective heterocyclization of unsymmetrical thioureas (1  a –1  q ). The synthesis was achieved at ambient temperature in good to excellent yields under catalyst free conditions. The molecular structures of 2‐ITZDs were elucidated by spectroscopic techniques such as FT‐ IR, 1 H‐ NMR and 13 C‐ NMR. X‐ray structural data was used to establish the structure (2  o ) unequivocally and to define the geometry of exo double bond. The in   vitro anticancer activity of 2‐ITZDs (2  a –2  q ) was investigated in several human cancer cell lines (A549, LNCap, PC‐3, MDA‐MB‐231, BxPC3, MIA PaCa2). All compounds showed cytotoxicity with IC50 values ranging from 6–23 μM in the tested cancer cell lines except MDA‐MB‐231. Compound 2  k (IC50 =7 μM) and the homologous analog 2  q (IC50 =6 μM) were found to be equipotent to 2  k and showed moderate cytotoxicity against human breast cell line (DA‐MB‐231). Furthermore, compound 2  k exhibited a medium permeability, enough metabolic stability and no significant inhibition of hERG channel. Compound 2  k inhibited cytochrome P450 activity below 50 % in 1 A2, 3 A4 and 2 C19, but not in 2 C9 and 2D6 at 10 μM. Structure‐activity relationships (SAR) provided useful insights towards this class of compounds and tiled a way to design novel analogues with increased potency. Abstract : A library of novel naphthoyl‐2‐ITZDs was prepared by regioselective heterocyclization and the structures were elucidated using spectroscopic and microanalytical data. X‐ray data established the structure (2  o) unequivocally and defined the geometry of exo double bond. In vitro studies against a panel of cell lines showed the potential of 2‐ITZDs as anti‐cancer analogs. Compound 2  k exhibited a medium permeability, and enough metabolic stability. A homologous analog 2  q (positional effect) was found equipotent to 2  k.